Get your photography on the Web : the fastest, easiest way to show & sell your work - Concepcion, Rafael ([Berkeley, California] : Peachpit Press, 2011)
Shows photographers how to set up and maintain a professional-looking website, covering such topics as securing a domain name and hosting space, installing WordPress, adding pictures and galleries, and selling images online
1. Domains & space: you need these first! -- 2. Getting your images ready -- 3. Using wordpress for your website -- 4. Adding content to your website -- 5. Plug-ins and menus to the rescue -- 6. HTML tips & tricks -- 7. Make your website pop with a theme -- 8. Printing your images online -- 9. Creating a flash-based portfolio -- 10. Using social media -- 11. Adding web galleries with FTP
Includes index
Keywords: Computer graphics -- Handbooks, manuals, etc; Photography -- Digital techniques -- Handbooks, manuals, etc; Web sites -- Design -- Handbooks, manuals, etc